2002
DOI: 10.1515/cclm.2002.010
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Serum Markers of Monocyte/Macrophage Activation in Type 1 Gaucher's Disease

Abstract: We studied 44 patients with type 1 Gaucher's disease (16 non-treated patients and 28 treated with enzyme replacement therapy). We measured serum levels of chitotriosidase (ChT), neopterin, angiotensin-converting enzyme (ACE), adenosine deaminase (ADA) and beta-hexosaminidase (Hex) and its major isoenzymes Hex A and Hex B. In the untreated group of patients, the increase in serum levels was ChT>neopterin>ACE> ADA>Hex, with all decreasing significantly in treated patients (p< 0.001). Highly significant correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 27 publications
1
17
0
1
Order By: Relevance
“…No statistically significant difference was found between serum chitotriosidase levels from smear-negative and culture-negative cases (accepted as sequel pulmonary tuberculosis for the purposes of this study) and those from healthy controls. It is known that serum chitotriosidase levels are generally under 18 nM/hour/mL in healthy people 8. Duplication during chitotriosidase gene activation is seen in approximately 5% of the general population, which makes it impossible to measure serum levels of the enzyme in patients with tuberculosis 9,10…”
Section: Discussionmentioning
confidence: 99%
“…No statistically significant difference was found between serum chitotriosidase levels from smear-negative and culture-negative cases (accepted as sequel pulmonary tuberculosis for the purposes of this study) and those from healthy controls. It is known that serum chitotriosidase levels are generally under 18 nM/hour/mL in healthy people 8. Duplication during chitotriosidase gene activation is seen in approximately 5% of the general population, which makes it impossible to measure serum levels of the enzyme in patients with tuberculosis 9,10…”
Section: Discussionmentioning
confidence: 99%
“…It should be mentioned that the serum markers for GD (Cox 2005;Deegan et al 2005) are considered to be produced and secreted by GCs (Hollak et al 1994), with the exception of the hex B marker, which has been suggested to come from hepatocytes (Casal et al 2002) altered by GlcCerase deficiency. It is worth noting that a massive systemic inflammation syndrome was induced in adult mice carrying the GD L444P mutation, which at the same time showed only minimal storage of GlcCer.…”
Section: Glucosylceramide Transfermentioning
confidence: 99%
“…Active synthesis of ACE in Gaucher cells may be responsible for the elevated enzyme levels in the serum and spleen of patients with Gaucher disease, while high levels of lysozyme may reflect an increased body mass of reticuloendothelial cells. In 16 patients with Gaucher disease not receiving enzyme therapy, increases in serum levels in decreasing order were observed for chitotriosidase, neopterin, ACE, adenosine deaminase and beta-hexosaminidase [10]. However, chitotriosidase and TRAP seem to be the only markers that do not overlap between patients and controls [30].…”
Section: Biochemical Markersmentioning
confidence: 99%